2015
DOI: 10.1007/s13197-015-1901-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of presoaking high hydrostatic pressure on the cooking properties of brown rice

Abstract: Effects of presoaking-high hydrostatic pressure (PHHP) on cooking time, hardness, gumminess, springiness, and microstructure of brown rice were evaluated. Compared with traditional soaking treatment, PHHP significantly shorten the cooking time of brown rice from 34 to 14 min. The hardness of brown rice treated by PHHP reduced remarkably, which is lower than that treated by soaking process and similar to that of white rice. The gumminess and springiness of brown rice dramatically decreased under pressure above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 30 publications
(39 reference statements)
0
16
0
1
Order By: Relevance
“…However, the effect of HPT on the color and textural properties of brown rice is limited. In a previous study from our lab (Yu et al 2015), it was found that single cycle HPT could shorten the cooking time and reduce the hardness of brown rice. However, this study was somewhat limited for concept testing with a single cycle HPT and lacked details on the influence on appearance, texture, morphology and market potential of HPT that might be possible with a two cycle HPT.…”
Section: Introductionmentioning
confidence: 88%
“…However, the effect of HPT on the color and textural properties of brown rice is limited. In a previous study from our lab (Yu et al 2015), it was found that single cycle HPT could shorten the cooking time and reduce the hardness of brown rice. However, this study was somewhat limited for concept testing with a single cycle HPT and lacked details on the influence on appearance, texture, morphology and market potential of HPT that might be possible with a two cycle HPT.…”
Section: Introductionmentioning
confidence: 88%
“…In this line, Ahromrit, Ledward, and Niranjan (2006) investigated HP-induced water uptake characteristics of glutinous rice (polished form), concluding that the equilibrium moisture content (EMC) and water uptake rates increased with pressure intensities (100-600 MPa) and temperature (20-70 ºC). Regarding WBR grains, however, the values for EMC fluctuated within the applied pressures of 100-500 MPa, which was related to the histochemical difference and the formed cracks at the RB surface (Yu et al, 2015). Yu et al (2015) reported that the HP-mediated pre-soaking contributed to shortening about 60% of the cooking time of WBR grains; and more importantly, the palatability was largely improved due to the damaged structure of pericarp and aleurone layer under pressures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Regarding WBR grains, however, the values for EMC fluctuated within the applied pressures of 100-500 MPa, which was related to the histochemical difference and the formed cracks at the RB surface (Yu et al, 2015). Yu et al (2015) reported that the HP-mediated pre-soaking contributed to shortening about 60% of the cooking time of WBR grains; and more importantly, the palatability was largely improved due to the damaged structure of pericarp and aleurone layer under pressures. These changes in cooking and textural attributes were greatly dependent on the applied pressure intensities (holding times and pressures) and processing patterns.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…GBR grains were boiled for 30 min and no white spots leaching were observed [5]. The cooked rice was placed in a 20-ml autosampler vial with a screw cap and the internal standard (IS), n-heptadecane, was added.…”
Section: Hs-spme Samplingmentioning
confidence: 99%